Task-sharing to support paediatric and child health service delivery in low- and middle-income countries: current practice and a scoping review of emerging opportunities - Zhao, Y; Hagel, C; Tweheyo, R; Sirili, N; Gathara, D; English, M (BioMed Central, 2021)
Background Demographic and epidemiological changes have prompted thinking on the need to broaden the child health agenda to include care for complex and chronic conditions in the 0–19 years (paediatric) age range. Providing such services will be undermined by general and skilled paediatric workforce shortages especially in low- and middle-income countries (LMICs). In this paper, we aim to understand existing, sanctioned forms of task-sharing to support the delivery of care for more complex and chronic paediatric and child health conditions in LMICs and emerging opportunities for task-sharing. We specifically focus on conditions other than acute infectious diseases and malnutrition that are historically shifted.